Classroom Management in Large and Mixed Ability Classes - Cristina Alina Soneriu (RATE Issues)
Teaching large and mixed ability classes is a real problem in most of the educational systems in the world and numberless attempts to address this issue have been made in time. It is a fact that achieving an atmosphere of interest, confidence, enthusiasm and mutual support in class is not easy. It involves failures and successes. The teacher must be willing and eager to make learning an exciting and creative experience. The article deals with some important aspects that the teacher should take into consideration in order to have a successful lesson.